THE POTENCIAL OF THE DUTCH CAVE AND JAPANESE CAVE FOREST PARK Ir. H. DJUANDA AS A PRODUCT OF DARK TOURISM BASED ON 4A TOURISM COMPONENT APPROACH - Oktaviani, Desy; Sutisna, Deden; Genia Fatihat, Gita; Hasan, Oliver; Yuliani, Reva (International Journal of Psychosocial Rehabilitation, 2020)
Bandung, in addition to having a diversity of potential attractions and natural tourism activities, also has a large share in the history of Indonesia after colonialism, so Bandung has a lot of history, both positive and negative. One of the historical relics in Bandung is the Dutch Cave and the Japanese Cave in the area of Taman Hutan Raya Juanda (Tahura Djuanda). Dark tourism, which is a special part of historical tourism because there are historical tourism destinations that bring memories of grief, sadness, and tragedy, has the potential to be developed in the Tahura DJuanda region. This qualitative study aims to identify the internal and external potential of the Dutch Cave and the Japanese Cave in supporting dark tourism in the city of Bandung. Premier data is obtained through in-depth interviews with managers and field staff on duty. Furthermore, in-depth interviews with the government on the extent of the policies and management of the Dutch cave and Goa Japan, including the obstacles encountered. The data obtained were then analyzed using the content analysis method approach to the 4A tourism component. This research can provide wider knowledge and insight related to the potential of dark tourism in the city of Bandung and can contribute in terms of the economy and the provision of large employment opportunities for the community. In addition, this research can be useful as input for relevant parties, especially policymakers who will develop dark tourism, so as to educate tourists about the sacrifice of people who strived for national independence. The research indicates that the Dutch Cave and Japanese Cave meet the criteria for dark tourism in the darkest spectrum because the caves have a dark history that occurred during the colonial period, where a tragic event that resulted in death occurred both during their construction and during their use.